PEMAHAMAN LINTAS BUDAYA SEBAGAI UPAYA MENINGKATKAN TOLERANSI SOSIAL DI INDONESIA: STUDI LITERATUR - Rahma Hidayati; Arlin Septia Basana Siagian; Stephanie Br Sipayung; Huraiyah Jiratullah; Mutiara Angelica Hasian Sihite; Tri Indah Prasasti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The cultural, ethnic, linguistic, and religious diversity of Indonesia presents both opportunities and challenges in building a harmonious social life. This study aims to examine the relationship between cross-cultural understanding and social tolerance in Indonesia through a systematic literature review. A qualitative approach with library research method was employed, using scientific articles, national and international journals, and conference proceedings published between 2022 and 2025 as data sources. Data were analyzed through content analysis and narrative synthesis, organized into four main themes. The findings reveal that: (1) ethnocentrism arising from limited cross-cultural understanding is the primary barrier to social tolerance; (2) constructive cross-cultural communication significantly contributes to the formation of tolerant attitudes; (3) digital media offers both opportunities and challenges for Generation Z's tolerance; and (4) multicultural education serves as a strategic pathway that has yet to be optimally implemented. This study concludes that strengthening cross-cultural understanding through integrated communication, digital, and educational approaches is crucial for fostering social tolerance in Indonesia's pluralistic society.